Awareness, perception and behavioral determinants associated with cancer prevention among adults: Results from a cross-sectional study in urban field practice area of a tertiary care hospital, Kolkata - Sarkar, Paramita; Pallabi Dasgupta; Sarkar, Payel; Rivu Basu (Asian Journal of Medical Sciences, 2024)
Background: Cancer is emerging as a major public health problem. Two-thirds of cancer patients are in the advanced stage at the time of diagnosis. Public awareness plays a big role in cancer prevention. Aims and Objectives: To assess awareness, perception, and behavioral determinants of cancer prevention of urban adults. Materials and Methods: An observational, cross-sectional study was conducted in the urban slum of Kolkata. Four hundred fifteen respondents were interviewed using a pre-tested questionnaire after having consent. Results: Though majority (72.3%) of respondents had satisfactory awareness but had limited awareness on screening tests (58.6%) and vaccination (1.6%). Half of them had a favorable perception on cancer prevention but the perceived barrier was more. The behavior score was poor among the majority of participants. The main source of information was T.V. (88.2%) and friends and relatives (80.2%). Only one-fourth of participants mentioned of health workers and health camps as sources of information indicating inadequate activities on cancer awareness programs. Age (OR 7.08, 95% CI=1.07–46.74), sex (OR 0.38, 95% CI=0.19–0.76) education (OR 4.81, 95% CI=2.50–9.27) were significant predictors of satisfactory awareness. Higher levels of education, younger age, and female gender were factors that shaped perception. Only education level (OR 0.29, 95% CI=0.15–0.59) had a significant association with cancer preventive behavior. Conclusions: Though awareness on primary preventive measures was satisfactory but behavior was unsatisfactory among study participants. They had more perceived barriers while taking preventive measures. The finding indicates a need to promote health education and motivate people to recognize and modify cancer-related behavioral risk factors.